2018
DOI: 10.1103/physrevb.97.075123
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations of the anisotropic optical properties of distorted 1TReS2 and ReSe2 monolayers, bilayers, and in the bulk limit

Abstract: We present a theoretical study of electronic and optical properties of the layered ReX 2 compounds (X = S, Se) upon dimensional reduction. The effect on the band gap character due to interlayer coupling is studied by means of self-energy corrected GW method for optimized and experimental sets of structure's data. Induced changes on the optical properties as well as optical anisotropy are studied through optical spectra as obtained by solving the Bethe-Salpeter equation. At the G 0 W 0 level of theory, when dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 61 publications
4
37
2
Order By: Relevance
“…Also, recent calculations showed that the fundamental band gap of ReS2 (ReSe2) strongly depends on the number of layers, which shifts from 2.38 eV (2.05 eV) for monolayers down to 1.60 eV (1.38 eV) for bulk, and remains direct. 29 Hence, despite it seems clear that while ReX2 exhibit somewhat structural and vibrational decoupled behavior, the electronic coupling is still significant.…”
Section: First-principle Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, recent calculations showed that the fundamental band gap of ReS2 (ReSe2) strongly depends on the number of layers, which shifts from 2.38 eV (2.05 eV) for monolayers down to 1.60 eV (1.38 eV) for bulk, and remains direct. 29 Hence, despite it seems clear that while ReX2 exhibit somewhat structural and vibrational decoupled behavior, the electronic coupling is still significant.…”
Section: First-principle Calculationsmentioning
confidence: 99%
“…23,26,27 Also, recent calculations show that the fundamental bandgap shrinks by 32.7% from monolayer to bulk and the interlayer binding energy is similar to other TMDCs such as MoS2. 29 On the other hand, optical, vibrational and structural measurements indicate that ReX2 exhibits a strong 2D character. For instance, PL measurements revealed that, in contrast with other TMDCs, emission energy barely shifts between monolayers and bulk (∆E ≈ −50 meV for ReS2 while ∆E ≈ −600 meV for MoS2), and the intensity increased with increasing the number of layers, rather than vanishing from a direct-to-indirect transition typically observed in conventional TDMCs.…”
Section: Introductionmentioning
confidence: 99%
“…This does not, however, affect the conclusion that ReSe 2 is indirect, since the CB minimum is still not co-located with the VBM; we find global indirect gaps in LDA, GGA respectively of 0.87 eV, 0.99 eV and a direct gap at Z of 0.97 eV, 1.00 eV. One other recent calculation gives an indirect gap of 0.92 eV for bulk ReSe 2 in the LDA with a direct quasiparticle gap at Z of 1.49 in the LDA+GdW approximation [27]; a second calculation in the GGA+GW approximation gives a direct gap at Z of 1.38 eV [26].…”
Section: Rhenium Sulphidementioning
confidence: 99%
“…For TMD materials, MoS 2 , MoSe 2 , WS 2 , WSe 2 , and MoTe 2 exhibit in‐plane isotropic optical and electrical behaviors . However, BP and its isoelectronic group IV MNs (SnS, SnSe, GeS, GeSe), ReSe 2 , ReS 2, and 2D perovskites show anisotropic behavior due to their puckered crystal lattices . Hence, strong light–matter interactions and reduced dimensionality lead to the formations of quasi‐2D excitons and trions in isotropic materials, and quasi‐1D excitons and trions in anisotropic materials .…”
Section: Introductionmentioning
confidence: 99%